Selective Harmonic Mitigation Technique for High-Power Converters - Napoles, Javier; Leon, Jose I; Portillo, Ramon; Franquelo, Leopoldo G; Aguirre, Miguel A (IEEE transactions on industrial electronics (1982), 2010)
In high-power applications, the maximum switching frequency is limited due to thermal losses. This leads to highly distorted output waveforms. In such applications, it is necessary to filter the output waveforms using bulky passive filtering systems. The recently presented selective harmonic mitigation pulsewidth modulation (SHMPWM) technique produces output waveforms where the harmonic distortion is limited, fulfilling specific grid codes when the number of switching angles is high enough. The related technique has been previously presented using a switching frequency that is equal to 750 Hz. In this paper, a special implementation of the SHMPWM technique optimized for very low switching frequency is studied. Experimental results obtained applying SHMPWM to a three-level neutral-point-clamped converter using a switching frequency that is equal to 350 Hz are presented. The obtained results show that the SHMPWM technique improves the results of previous selective harmonic elimination pulsewidth modulation techniques for very low switching frequencies. This fact highlights that the SHMPWM technique is very useful in high-power applications, leading its use to an important reduction of the bulky and expensive filtering elements.